HUBUNGAN BODY COMPARISON TERHADAP IDOL K-POP DENGAN PERILAKU MAKAN TIDAK SEHAT PADA REMAJA PUTRI DI JAKARTA - Irfanty Ayu Widhianjani (2020)
Adolescence is a transition to adulthood that is marked by physical, psychological and cognitive changes. The majority of young women pay attention to their body shapes and compare them with their role models, such as K-Pop idols. Some of these young women try to look like their idols by changing their eating behavior. This study aims to determine the relationship of body comparison toward K-Pop idols with unhealthy eating behavior (restraint eating, emotional eating and external eating) in female adolescents in Jakarta. This research uses a quantitative approach with cross sectional design. The sampling technique uses a type of nonprobability sampling method that is volunteer sampling through social media twitter to 222 female adolescents using the chi-square test. The body comparison research instrument uses the Body Comparison Scale (BCS) and unhealthy eating behavior using the Dutch Eating Behavior Questionnaire (DEBQ-32). The analysis showed that body comparison with K-pop idols did not have a significant relationship with total 116 respondents restraint eating (52.3%) (p = 0.286), total 119 respondents emotional eating (53.6%) (p = 0.780) and total 116 respondents external eating (53.6%) (p = 0.286). This shows that there is no relationship between body comparison with K-pop idols on restraint eating, emotional eating, and external eating in female adolescents in Jakarta.